Meso‐Substituted Tetrabenzotriazaporphyrins for Dye‐Sensitized Solar Cells. Issue 8 (3rd August 2020) - Tejerina, Lara; Yamamoto, Satoshi; López‐Duarte, Ismael; Martínez‐Díaz, M. Victoria; Kimura, Mutsumi; Torres, Tomás
Abstract: A novel tetrabenzotriazaporphyrin (TBTAP) bearing an anchoring carboxy‐phenyl group at the meso ‐carbon position (TT260 ) was synthesized by an efficient method, which involves the crossover condensation between phthalonitrile and aminoisoindoline precursors. Its optical and electrochemical properties were also investigated together with its use as sensitizer in dye‐sensitized solar cells (DSSCs). The performance of TT260 was compared with a benchmark molecule TT1, bearing similar bulky tert‐ butyl groups at the periphery. The device, which is the first ever example of meso ‐substituted TBTAP‐based DSSC, exhibits a modest maximum power conversion efficiency of 2.4±0.1 % under one‐sun conditions. Abstract :